Interiors of the Mahanaleshwar Temple - Temples of India Project Team (Jio Institute, 2024)
The principal entrance of the Mahanaleshwar Temple is flanked by a row of pillars and dwarf walls. This is the mukhamandapa (front porch) of the temple which is connected to the closed mandapa (pillared hall). The dwarf walls of the kakshasana (seat backs) have small pillar posts.